Kolb’s method in teaching for the development of listening skills in young learner - Bazan Suarez, Diego Arturo (2023)
Currently, studying a new language turns out to be a challenge that undoubtedly requires a lot of effort, sacrifice, and dedication; however, unlike having a mother tongue, a second language gives us the opportunity to visualize open doors and opportunities that many times are dreams that people have always longed for, just as the English language is an intermediary of many possible opportunities. This research project is based on the development of the learning process in high school and focuses on the methodologies and strategies that each English teacher can apply to transmit their knowledge to the students. Also, it emphasizes the use of Kolb´s method with the objective of determining the different scenarios in which the students learn. Furthermore, in order to develop this research project, it is necessary to consider the numerous influential factors, such as the distractors, motivation, efforts, skills, abilities, and main objectives, which are the main foundations on which a teacher can carry out an effective work. Finally, the aim of this research project is to demonstrate that students don´t learn in the same way, and they need to innovate the teaching and learning process.